2012
DOI: 10.1039/c2cc31576a
|View full text |Cite
|
Sign up to set email alerts
|

Compositional dependence of the stability of AuCu alloy nanoparticles

Abstract: The oxidation of AuCu nanoparticles was studied as a function of composition and temperature. Oxidation rates at 110 °C were higher for NPs with higher Cu content, showing that Au stabilized the Cu. Electrochemistry measurements show that AuCu could be a promising catalyst for lowering the over potential of CO(2) reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
157
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 35 publications
8
157
0
1
Order By: Relevance
“…1c). The SPR peaks (l SPR ¼ 533 nm for Au 3 Cu, 539 nm for AuCu and 549 nm for AuCu 3 ) also match well with their composition 26,30 . Energy-dispersive X-ray spectroscopy was further used to confirm the composition of the nanoparticles ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…1c). The SPR peaks (l SPR ¼ 533 nm for Au 3 Cu, 539 nm for AuCu and 549 nm for AuCu 3 ) also match well with their composition 26,30 . Energy-dispersive X-ray spectroscopy was further used to confirm the composition of the nanoparticles ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 48%
“…Au and Cu nanoparticles in their pure phase exhibit characteristic surface plasmon resonance (SPR) peaks at B523 and B570 nm (refs 26,30,31). As the content of Cu increases in a pure Au nanoparticle by forming an alloy, the SPR peak of Au red-shifts towards the SPR peak of Cu with some broadening 26,30 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu nanoparticles (NPs) could be beneficial in facilitating the CO 2 reduction reaction but their instability caused by combined effects of aggregation and rapid deactivation of the catalytic surface via oxidation has limited their consideration. One strategy recently proposed to overcome the stability issues was to use Au 2 Cu NPs that are less prone to oxidation instead Cu NPs for CO 2 reduction [18]. However, Au is expensive and also known to be a good catalyst for HER that can disrupt the production of hydrocarbons [19].…”
Section: Introductionmentioning
confidence: 99%
“…The Au-Cu alloy catalysts are significantly more active than monometallic Cu and Au catalysts, because there is a synergistic interaction between Cu and Au, and Cu can facilitate the activation of molecular oxygen [23,24]. Zhang et al reported that Au-Cu alloy nanoparticles highly dispersed in the channels of SBA-15 are highly sintering-resistant even at high temperature treatment, and have much better catalytic performance than monometallic particles in catalytic CO oxidation, due to the synergistic effect between Au and Cu [25].…”
Section: Introductionmentioning
confidence: 99%